Higher education, governance and national scientific identity - Moquillaza-Sánchez, Janina (2024)
This theoretical-critical reflection addresses the issue of national scientific identity, focusing on the current crisis involving the National Superintendence of Higher University Education (SUNEDU, by its Spanish acronym), the Ministry of Education of Peru (MINEDU), and the Congress of the Republic of Peru. With the objective to understand the imbalance on stage and its consequences for university education, we analyze idiosyncrasies that jeopardize links of social responsibility, environmental concern, and scientific ethics. Drawing upon Bachelard (2005; 2000), Enaudeau (1999), La Boétie (1999), Bauman (1999), and Sánchez (2022a; 2022b; 2019; 2017), we propose dialogical interactions between governamental institutions and the science produced by Peruvian and Latin American public universities in general. This is facilitated through the exchange among study groups, research cores, and scientific observatories contributing to governance with social justice and maintaining links of scientific identity and the Andean principle of allin kawsay for everyone.